Correlative Fluorescence and Electron Microscopy. Issue 1 (1st October 2014) - Schirra, Randall T.; Zhang, Peijun
Abstract: Correlative fluorescence and electron microscopy (CFEM) is a multimodal technique that combines dynamic and localization information from fluorescence methods with ultrastructural data from electron microscopy, to give new information about how cellular components change relative to the spatiotemporal dynamics within their environment. In this review, we will discuss some of the basic techniques and tools of the trade for utilizing this attractive research method, which is becoming a very powerful tool for biology labs. The information obtained from correlative methods has proven to be invaluable in creating consensus between the two types of microscopy, extending the capability of each, and cutting the time and expense associated with using each method separately for comparative analysis. The realization of the advantages of these methods in cell biology has led to rapid improvement in the protocols and has ushered in a new generation of instruments to reach the next level of correlation—integration. Curr. Protoc. Cytom . 70:12.36.1‐12.36.10. © 2014 by John Wiley & Sons, Inc.